2021
DOI: 10.3390/jcm10091940
|View full text |Cite
|
Sign up to set email alerts
|

Association of Immune Thrombocytopenia and Inflammatory Bowel Disease in Children

Abstract: Background: The association between inflammatory bowel disease (IBD) and immune thrombocytopenia (ITP) is still uncertain. In this multicenter retrospective study, the coexistence of both diseases was investigated in children diagnosed from 1 January 2000 to 31 December 2019. Methods: Clinical characteristics of both IBD and ITP, onset of disorders, and patient’s response to treatment were collected through a structured form sent to 55 Italian pediatric referring centers for hematological disorders. Result: Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The higher incidence of ITP in childhood rather than in adulthood leads us to move away from the hypothesis that ITP is a consequence of IBD. However, this hypothesis, as demonstrated by Guarina et al (2021), cannot be excluded since, in pediatric patients, there was complete recovery from ITP after undergoing colectomy [56]. In other patients, a combination of IBD exacerbation and lowering of the platelet count was observed.…”
Section: Inflammatory Bowel Diseases: How Can Garlic Be Beneficial?mentioning
confidence: 95%
See 1 more Smart Citation
“…The higher incidence of ITP in childhood rather than in adulthood leads us to move away from the hypothesis that ITP is a consequence of IBD. However, this hypothesis, as demonstrated by Guarina et al (2021), cannot be excluded since, in pediatric patients, there was complete recovery from ITP after undergoing colectomy [56]. In other patients, a combination of IBD exacerbation and lowering of the platelet count was observed.…”
Section: Inflammatory Bowel Diseases: How Can Garlic Be Beneficial?mentioning
confidence: 95%
“…Another important consideration is that several antibody-induced autoimmune hematologic diseases, such as immune thrombocytopenia (ITP), characterized by platelet destruction by antibodies, have occasionally been observed in patients with IBD [56]. In fact, more and more scientists are conducting studies in order to understand the correlation of these two diseases.…”
Section: Inflammatory Bowel Diseases: How Can Garlic Be Beneficial?mentioning
confidence: 99%
“…Journal of Inflammation Research 2022:15 6376 reported to be of therapeutic benefit in children with UC comorbid with ITP. 37 In Guarina et al 37 's case series of eight children with comorbid UC and ITP, two cases underwent colectomy and the ITP recovered postoperatively in one of them.…”
Section: Dovepressmentioning
confidence: 99%
“…In this article, we presented two cases of two comorbidities (HES and ITP) occurring in the context of chronic active UC and responding only to surgical colectomy. Though several cases of HES 18,[25][26][27][28] and ITP 14,23,[29][30][31][32][33][34][35][36][37][38][39] have been reported to co-occur with UC, the patients described in this article are unique in their presentation and treatment response. To the best of our knowledge, they represent rare cases of refractory comorbidities in the context of UC that failed conventional medical therapy and responded only to surgical treatment.…”
Section: Conclusion and Rationalementioning
confidence: 99%
See 1 more Smart Citation